Utilization of Clean Water, Personal Hygiene of Toddler Caregivers, and Smoking Behavior of Family Members as Risk Factors for Cases of Stunting Toddlers - Milada Mohammad Ravsanjanie; Aditya Sukma Pawitra; Khuliyah Candraning Diyanah; Zainul Amiruddin Zakaria; Najihah Hanisah BTE Marmaya (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: Pasuruan District was in the 7th rank of the highest stunting prevalence in the East Java Province (39.7%). Stunting cases that are not handled properly lead to the decrease of cognitive and motor skills, productivity, and even lead to death. One of the risk factors for stunting cases is a history of infection with toddlers (or children under five) from poor behavior of family and caregiver. The purpose of this study was to analyze the effect of clean water use, personal hygiene for toddler caregivers, and the smoking behavior of family members in cases of stunting toddlers in Pasuruan District. Methods: The research was conducted using a case-control design with a ratio of 1: 1. Sampling using stratified random sampling and the proportion of 2% of 2,718 toddlers. Toddlers with z-scores <-3SD – <-2SD became a case group of 118 and toddlers with z-scores â‰¥-2SD – 2SD became controls of 114. Results and Discussion: There was an effect between smoking inside the house (p = 0.004, OR = 0.473), dishes and drinking utensils washed with soap and running water (p = 0.029, OR = 2.726), washing hands with soap and running water by caregivers (p = 0.002, OR = 2.52), and cutting fingernails by caregivers (p = 0.006, OR = 0.544) on cases of stunting toddlers. Conclusion: Clean water utilization, personal hygiene of toddler caregivers, and the smoking behavior of family members are the risks in the incidence of stunting toddlers in Pasuruan District. The variable of dishes and drinking utensils washed with soap and running water is the highest risk (OR = 2.726) for cases of stunting toddlers in Pasuruan District. The food and drink utensils that are not washed properly and correctly will allow bacterial contamination which causes toddlers to become infected.